Experiences and perceptions of ageing among older First Nations Australians: A rapid review. (14th December 2021) - Yashadhana, Aryati; Howie, Adam; Veber, Madelene; Cullen, Patricia; Withall, Adrienne; Lewis, Ebony; McCausland, Ruth; Macniven, Rona; Andersen, Melanie
Abstract: Objective: To identify and describe articles reporting the experiences and perceptions of ageing among older First Nations Australians. Methods: Following rapid review and PRISMA guidelines, we searched five databases for peer‐reviewed articles published prior to October 2019 that reported qualitative accounts of ageing among older (≥ 45 years) First Nations Australians. Data were extracted and synthesised thematically. Results: Twenty‐one articles were included in the final synthesis. Priorities in ageing highlighted the role of Elders, family, community, culture and connection to ancestral lands. Experiences and perceptions of ageing reflected cultural marginalisation in aged and health care services, and highlighted the importance of cultural identity, resilience and survival as key to ageing well. Conclusions: Our review suggests that mainstream ageing frameworks do not fully reflect the priorities of older First Nations Australians. This has important implications for ageing policy and the design and delivery of culturally safe aged and health care services.